Perioperative systemic therapy for resectable colorectal peritoneal metastases: Sufficient evidence for its widespread use? A critical systematic review - Rovers, Koen P.; Simkens, Geert A.; Punt, Cornelis J.; van Dieren, Susan; Tanis, Pieter J.; de Hingh, Ignace H. (Critical reviews in oncology/hematology, 2017)
•(Neo)adjuvant systemic therapy is widely used as adjunct to cytoreduction/HIPEC.•In colorectal peritoneal metastases, evidence supporting its use is strikingly scarce.•The widespread use of (neo)adjuvant systemic therapy in this setting may be questioned.•Randomised intention-to-treat studies on this topic are highly warranted.•Included studies may suggest a role for neoadjuvant systemic therapy. Despite its widespread use, no randomised studies have investigated the value of perioperative systemic therapy as adjunct to cytoreduction and HIPEC for colorectal peritoneal metastases. This systematic review evaluated the available evidence, which consists of non-randomised studies only. A systematic search identified studies that investigated the influence of neoadjuvant, adjuvant, or perioperative systemic therapy on overall survival (OS). The 11 included studies (n=1708) were clinically heterogeneous and subject to selection bias. Studies on neoadjuvant systemic therapy revealed OS benefit (n=3), no OS benefit (n=1), and superiority of chemotherapy with bevacizumab vs. chemotherapy (n=2). Studies on adjuvant systemic therapy showed no OS benefit (n=3). Studies on perioperative systemic therapy demonstrated OS benefit (n=1), and superiority of modern vs. conventional systemic therapy(n=1). Significant limitations of available evidence question the widespread use of perioperative systemic therapy in this setting, stress the need for randomised studies, and impede conclusions regarding optimal timing and regimens. Included studies may suggest a survival benefit of neoadjuvant systemic therapy.